Forestry and no net loss principle. The possibilities and need to implement NNL in forest management in Finland - Minna Pappila (Gabriel Michanek, 2022)
Biodiversity is declining all over the world, although there are numerous conventions, policies, and strategies for tackling the problem. One way to approach the imminent problem is to use the no net loss (NNL) of biodiversity principle to help to prevent harm to biodiversity. The NNL principle urges the prevention of biodiversity losses during and after the completion of a development project orother land-use. According to mitigation hierarchy, losses should be first avoided and then minimized, and if possible, restored on the spot. If biodiversity loss occurs despite preventive measures, it must be fully compensated to create a no net loss situation. In this article, Finnish legislation and soft law regulation concerning forest management is scrutinized within the framework of the NNL principle. Theanalysis shows that there are many shortcomings inFinnish forest and nature protection regulation at all levels of mitigation hierarchy. Overall, the NNL principle proves to be useful for evaluating the ecological sustainability of ongoing land use such as forest management.